Construction of Ethical Religiosity as a Marketing Strategy for Maqoo Halal Products Z Generation Muslim Consumers in Jombang - Efendi, Rofik; Abitolkha, Amir Maliki; Abdulghani, Naser Ali (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2025)
Purpose:This study examines how Islamic religious streams in Jombang market halal Maqoo mineral water to Generation Z Muslims by reconstructing religiosity through the integration of ethical and economic values. The findings reveal that consumer engagement is shaped less by doctrinal obligation and more by an ethical economic synergy, offering new insights into Islamic marketing and consumerism.Design/Methodology:The study employs a qualitative method, drawing data from Maqoo halal water business actors within the Shiddiqiyah tarekat, its congregants, and randomly selected Generation Z Muslim consumers in Jombang. Chosen as the research locus for its pesantren culture and unique intertwining of spiritual authority and economic activity, Jombang provides a context to examine how ethical religiosity is constructed as younger Muslims negotiate between spiritual values and economic rationality in halal consumption.Findings:The research findings show that Maqoo's halal product marketing strategy integrates strong ethical religiosity values, aligned with the spiritual aspirations of Z Generation Muslim consumers. Ethical construction through educational, symbolic, and social approaches that emphasize aspects of blessing, social responsibility, and personal piety. Practical Implications:The implications of this study illustrate that Generation Z consumers are influenced not only by the halal quality and functional excellence of products, but also by social contributions and the reputation of the corporate brand.Originality/Value:This research highlights that the construction of religiosity in marketing is not merely an additional element but becomes the core of the product narrative, shaping consumers’ emotional and spiritual loyalty. The findings imply that the effectiveness of halal product marketing strategies for Muslim Generation Z depends on a brand’s ability to integrate ethical values, social responsibility, and authenticity in communication.